Targeting functional fitness, hearing and health-related quality of life in older adults with hearing loss: Walk, Talk 'n' Listen, study protocol for a pilot randomized controlled trial. Issue 1 (December 2017) - Lambert, Justin; Ghadry-Tavi, Rouzbeh; Knuff, Kate; Jutras, Marc; Siever, Jodi; Mick, Paul; Roque, Carolyn; Jones, Gareth; Little, Jonathan; Miller, Harry; Van Bergen, Colin; Kurtz, Donna; et al.
Abstract Background Hearing loss (HL) is a disability associated with poorer health-related quality of life including an increased risk for loneliness, isolation, functional fitness declines, falls, hospitalization and premature mortality. The purpose of this pilot trial is to determine the feasibility and acceptability of a novel intervention to reduce loneliness, improve functional fitness, social connectedness, hearing and health-related quality of life in older adults with HL. Methods This 10-week, single-blind, pilot randomized control trial (RCT) will include a convenience sample of ambulatory adults aged 65 years or older with self-reported HL. Following baseline assessments, participants will be randomized to either intervention (exercise, health education, socialization and group auditory rehabilitation (GAR)) or control (GAR only) groups. The intervention group will attend a local YMCA twice a week and the control group once a week. Intervention sessions will include 45 min of strengthening, balance and resistance exercises, 30 min of group walking at a self-selected pace and 60 min of interactive health education or GAR. The control group will attend 60-min GAR sessions. GAR sessions will include education about hearing, hearing technologies, enhancing communication skills, and psychosocial support. Pre-post trial data collection and measures will include: functional fitness (gait speed, 30-s Sit to Stand Test), hearing and health-related quality of life, loneliness, depression, social participation and social support. At trial end, feasibility (recruitment, randomization, retention, acceptability) and GAR will be evaluated. Discussion Despite evidence suggesting that HL is associated with declines in functional fitness, there are no studies aimed at addressing functional fitness declines associated with the disability of HL. This pilot trial will provide knowledge about the physical, mental and social impacts on health related to HL as a disability. This will inform the feasibility of a larger RCT and preliminary evidence about the initial effects of a novel, community-based, holistic intervention addressing both the negative psychosocial and functional physical effects of HL among older adults. Trial registration ClinicalTrials.gov, NCT02662192 . Registered on 14 January 2016